Fuerza de salto vertical en jugadores de voleibol varones de distinto nivel competitivo - Saavedra, Hernan Blasco (2017)
In the team sports players must repeat sequences of explosive movements of short duration with this an important place during the course of the game. The aim of this study was to evaluate and compare the power strength Lower Limbs in the volleyball players according to the level. Materials and Methods: The present study is descriptive, comparative, cross-sectional study. The sample is composed of 42 male volleyball players, with average values of Weight 81.73 + 9,54 (Kg), height 186.06 + 0.79(cm). The subjects carried out three types of vertical jump on the contact plataform, abalakov (ABK), Countermovement jump(CMJ) and Squat jump (SJ) without countermovement (SJ), to evaluate the power strength of the lower limbs. To the check significant differences between the groups in each one of the variables used one-way ANOVA and the Tukey test specificity (p<0.05). Results:Significant differences were found p<0.01 in the age, height, Index of elasticity and in the SJ. In the rest of the variables are not significant differences. Conclusion:The statistically significant differences were observed, favorable to the team from the University of Concepcion, in comparison on the selection adult and youth of Chile in the three vertical jumps